AN INVESTIGATION OF LOCAL WISDOM TO SUPPORT ADULT LITERACY PROGRAM - Laksono, Bayu Adi; ., Supriyono; Wahyuni, Sri (PEOPLE: International Journal of Social Sciences, 2018)
This research is aimed at investigating the function of local wisdom as a supporting element to the implementation of the adult literacy program in Jember regency, East Java, Indonesia. Indonesia government have an adult literacy program to reduce the level of illiteracy, it called functional literacy. The level of illiteracy of Jember regency is statistically high and the people adhere strongly to the existed local wisdom. The study used a qualitative approach. The data was collected by using interview, observation, and documentation. From the research finding it was found that there were 14 local wisdoms that can be explored from Jember Regency. Local Wisdoms were used to teaching and learning material and facilitate learning trigger. There were 7 local wisdoms can be used as the teaching and learning material. The other 7 local wisdoms were used to facilitate learning trigger. The indicator of the local wisdom uses for supporting the learning process of functional literacy program is under the principle of the design principle and local context.